Extraction of antioxidant polysaccharide from Ancanthohora spp. optomization using response surface methodology (RSM). - Gonzales, Seasha G. (2023.)
Ancathophora spp. is a wild underutilized carrageenophyte in the Philippines with potential antioxidant properties. With intention to explore one of its bioactive properties, advocacy for its cultivation and application is deemed forward response. Geared with response surface methodology (RSM) of Design ExpertⓇ, this study aimed at optimizing extraction conditions using independent variables, KOH concentration (%), hydrolysis temperature (℃), and extraction time (h). Their various interactions on the in vitro antioxidant activities (e.g., DPPH, FRAP, and ABTS assays) of carrageenan extracts were investigated. The moisture content was also determined to analyze samples on a dry-weight basis. Results found that the optimum conditions for DPPH (31.99%) and FRAP (0.09) inhibitions are at 3% KOH concentration at 85℃ for 3 h. ABTS inhibition (72.07%) was highest at 3% KOH concentration at 65 (℃) for 3 h. The highest moisture content (14.42%) was observed at 3% KOH concentration at 85 (℃) for 2 h. The optimized combination of conditions shows that when KOH concentration is minimized, time is maximized, and temperature is maximized, the desirability of DPPH, FRAP, ABTS, and moisture content ranges from 0.955 to 0.958, which is close to 1. These designing conditions can be manipulated in alkali extraction of carrageenan to yield higher moisture content and higher antioxidant activity.
Thesis (Undergraduate, Bachelor of Science in Fisheries) College of Fisheries and Ocean Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2023.
Keywords: Ancanthophora; Antioxidants